2019
DOI: 10.1016/j.talanta.2019.05.106
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pesticide residues in honeybee (Apis mellifera L.) and in corbicular pollen. Exposure in citrus orchard with an integrated pest management system

Abstract: In the last years, the honeybee population is facing growing threats such as expansion 4 of pathogens, the incorrect use of phytosanitary products and environmental 5 contaminants, loss or fragmentation of habitat, invasive species and climate change. In 6 Spain, the citrus cultivation in integrated pest management (IPM) attempts the most 7 available use of strategies for the control of pests populations by means of taking 8 actions that prevent problems, remove levels of damage and use of chemical control 9 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Dietary exposure via the consumption of pollen and nectar is undoubtedly an important route of exposure for the bee larvae. Pyriproxyfen has been found in various pollen samples up to about 40 µg/kg [130][131][132][133]135,136]. The number of studies on pesticide residues in nectar samples is rather limited and to the best of our knowledge, pyriproxyfen was never analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary exposure via the consumption of pollen and nectar is undoubtedly an important route of exposure for the bee larvae. Pyriproxyfen has been found in various pollen samples up to about 40 µg/kg [130][131][132][133]135,136]. The number of studies on pesticide residues in nectar samples is rather limited and to the best of our knowledge, pyriproxyfen was never analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Vidau [132] detected pyriproxyfen in 11.1% of the pollen samples analyzed (LOQ = 10 µg/kg) while Calatayud-Vernich et al [133] found pyriproxyfen in one of the 45 pollen samples analyzed at a concentration of 6 µg/kg and in 12% of the beebread samples analyzed (n = 33) at concentrations ranging from 1 to 5 µg/kg [134]. During a two-year study performed in IPM (integrated pest management) citrus orchards, Garcia-Valcárcel et al [135] found pyriproxyfen at concentrations up to 43.2 µg/kg in fresh pollen samples and up to 3.4 µg/kg in honey bees. Lastly, among 155 fresh pollen samples collected from September 2012 to August 2013 in 14 monitoring apiaries in Taiwan, Nai et al [136] found pyriproxyfen only once at a concentration of 40 µg/kg (LOD = 10 µg/kg).…”
Section: Lethal Sublethal and Behavioral Effects At The Hive Levelmentioning
confidence: 98%
“…However, the spread of pests leads to severe losses of crops, which probably results in a severe decline in the overall economy. Integrated pest management has significant socioeconomic importance in the agricultural production sector, relying on comprehensive strategies to protect production from pest disasters (García-Valc arcel et al, 2019). However, there are many pieces of evidence to connect spraying pesticides with health issues.…”
Section: Related Workmentioning
confidence: 99%
“…Numerous authors have analysed pesticide residues in pollen. García-Valcárcel et al (2019) analysed 10 active substances in pollen samples in Spain. Vázquez et al (2015) analysed 253 active substances in pollen samples in Spain.…”
Section: Introductionmentioning
confidence: 99%